Antibacterial activity of bioactive compound produced by endophytic fungi isolated from Mangifera casturi Kosterm endemic plant from South Kalimantan, Indonesia - Fatia Rizki Nuraini; Ratna Setyaningsih; Ari Susilowati (Indonesian Journal of Biotechnology, 2023)
The endophytic fungi that live in endemic plants are a promising bio‐prospect as the producers of antibacterial compounds. This research is aimed to evaluate the endophytic fungi antibacterial compound from Mangifera casturi. The bioactive compounds of 13 endophytic fungi were extracted using ethyl acetate and evaluated for antibacterial activity using disk diffusion assay. The minimum inhibitory concentration (MIC) was measured using the serial broth dilution method. Scanning Electron Microscopy (SEM) was used to examine cell damage because of the extract. The antibacterial compounds were then detected using GC‐MS analysis. The endophytic fungi were identified morphologically and molecularly based on ITS rDNA sequencing Among the 13 isolates, the endophytic fungi identified as Botryosphaeria rhodina AK32 produced the antibacterial compounds that exhibited the highest activity and a broad spectrum. Moreover, they were capable against resistant bacteria, Methicillin Resistant Staphylococcus aureus (MRSA) with an MIC value of 1.56% for all the test bacteria. The mechanism of action of AK32 ethyl acetate extract seemed to affect the condition of bacterial cell walls, causing morphological alteration such as shrinkage of the cell, warted cells, and hollow cells. Based on GC‐MS, the antibacterial compounds of AK32 ethyl acetate extract were di‐n‐octyl phthalate, benzyl alcohol, high‐oleic (CAS) safflower oil, benzene acetonitrile, and benzotriazole.